=>3x^4-9x^2-x^2+3=0
=>(x^2-3)(3x^2-1)=0
hay \(x\in\left\{\sqrt{3};-\sqrt{3};\dfrac{\sqrt{3}}{3};-\dfrac{\sqrt{3}}{3}\right\}\)
=>3x^4-9x^2-x^2+3=0
=>(x^2-3)(3x^2-1)=0
hay \(x\in\left\{\sqrt{3};-\sqrt{3};\dfrac{\sqrt{3}}{3};-\dfrac{\sqrt{3}}{3}\right\}\)
giải phương trình \(10x^2-9x-8x\sqrt{2x^2-3x+1}+3=0\)
Giải phương trình:
1. \(x^3-3x^2-9x+12=0\)
2. \(x^4-x^3+18x^2-3x+9=0\)
3. \(\left(x^2-3x+3\right)^2-3x^2+8x-6=0\)
4. \(\left(2x^2-5x+1\right)^2-10x^2+24x-4=0\)
5. \(\left(x-3\right)\left(x-1\right)\left(x+2\right)\left(x+6\right)-40x^2=0\)
Giải phương trình nghiệm nguyên \(3x^2+5xy-8x-2y^2-9y-4=0\)
giải phương trình:
1, x4 - 2x3 + x - \(\sqrt{x\left(x^2-x\right)}\) = 0
2, \(\sqrt{x^2-3x+2}=\sqrt{10x-20}-\sqrt{x-3}\)
Giải phương trình sau
a) \(x^4+5x^3-10x^2+10x+4=0\)
b) \(x^4-8x^2+x+12=0\)
Giải phương trình:
a) \(x^3-3x^2-9x+12=0\)
b) \(\left(x-3\right)^4+\left(x+1\right)^4=82\)
c) \(x^4-10x^3+25x^2-20x+4=0\)
d) \(2x^4+12x^3+7x^2-33x+5=0\)
e) \(\left(x^2-3x+3\right)^2-3x^2+8x-6=0\)
f) \(\left(x-3\right)\left(x-1\right)\left(x+2\right)\left(x+6\right)-40x^2=0\)
Giải phương trình:
1. \(x^2+3x+8=\left(x+5\right)\sqrt{x^2+x+2}\)
2. \(10x^2-9x-8x\sqrt{2x^2-3x+1}+3=0\)
3. \(x^3+6x^2-2x+3-\left(5x-1\right)\sqrt{x^3+3}=0\)
4. \(4\sqrt{x+1}-1=3x+2\sqrt{1-x}+\sqrt{1-x^2}\)
5. \(4\sqrt{x+3}=1+4x+\dfrac{2}{x}\)
\(9x^4+3x^3-10x^2-5x+25=0\)
Giải giúp mình với
Giải phương trình
\(\sqrt{2\left(x^4+4\right)}=3x^2-10x+6\)